Risk factors for and perinatal outcomes of major depression during pregnancy: a population-based analysis during 2002–2010 in Finland. Issue 11 (14th November 2014) - Räisänen, Sari; Lehto, Soili M; Nielsen, Henriette Svarre; Gissler, Mika; Kramer, Michael R; Heinonen, Seppo
Abstract : Objectives: To identify risk factors for and the consequences (several adverse perinatal outcomes) of physician-diagnosed major depression during pregnancy treated in specialised healthcare. Design: A population-based cross-sectional study. Setting: Data were gathered from Finnish health registers for 1996–2010. Participants: All singleton births (n=511 938) for 2002–2010 in Finland. Primary outcome measures: Prevalence, risk factors and consequences of major depression during pregnancy. Results: Among 511 938 women, 0.8% experienced major depression during pregnancy, of which 46.9% had a history of depression prior to pregnancy. After history of depression, the second strongest associated factor for major depression was fear of childbirth, with a 2.6-fold (adjusted OR (aOR=2.63, 95% CI 2.39 to 2.89) increased prevalence. The risk profile of major depression also included adolescent or advanced maternal age, low or unspecified socioeconomic status (SES), single marital status, smoking, prior pregnancy terminations, anaemia and gestational diabetes regardless of a history of depression. Outcomes of pregnancies were worse among women with major depression than without. The contribution of smoking was substantial to modest for small-for-gestational age newborn (<−2 SD below mean birth), low birth weight (<2500 g), preterm birth (<37 weeks) and admission to neonatal intensive care associated with major depression, whereas SES made only a minor contribution. Conclusions: Physician-diagnosed major depression during pregnancy was found to be rare. The strongest risk factor was history of depression prior to pregnancy. Other associated factors were fear of childbirth, low SES, lack of social support and unhealthy reproductive behaviour such as smoking. Outcomes of pregnancies were worse among women with major depression than without. Smoking during pregnancy made a substantial to modest contribution to adverse outcomes associated with depression during pregnancy.